Visions of paradise : images of Eden in the cinema - Dixon, Wheeler W., 1950- (ACLS Humanities E-Book., 2006)
Depictions of sex, violence, and crime abound in many of today's movies, sometimes making it seem that the idyllic life has vanished-even from our imaginations. But as shown in this unique book, paradise has not always been lost. For many years, depictions of heaven, earthly paradises, and utopias were common in popular films. Illustrated throughout with intriguing, rare stills and organized to provide historical context, Visions of Paradise surveys a huge array of films that have offered us glimpses of life free from strife, devoid of pain and privation, and full of harmony. In films.